Diverse Deformation Mechanisms and Lithologic Controls in an Active Orogenic Wedge: Structural Geology and Thermochronometry of the Eastern Greater Caucasus. Issue 12 (16th December 2022) - Tye, A. R.; Niemi, N. A.; Cowgill, E.; Kadirov, F. A.; Babayev, G. R.
Abstract: Orogenic wedges are common at convergent plate margins and deform internally to maintain a self‐similar geometry during growth. New structural mapping and thermochronometry data illustrate that the eastern Greater Caucasus mountain range of western Asia undergoes deformation via distinct mechanisms that correspond with contrasting lithologies of two sedimentary rock packages within the orogen. The orogen interior comprises a package of Mesozoic thin‐bedded (<10 cm) sandstones and shales. These strata are deformed throughout by short‐wavelength (<1 km) folds that are not fault‐bend or fault‐propagation folds. In contrast, a coeval package of thick‐bedded (up to 5 m) volcaniclastic sandstone and carbonate, known as the Vandam Zone, has been accreted and is deformed via imbrication of coherent thrust sheets forming fault‐related folds of 5–10 km wavelength. Structural reconstructions and thermochronometric data indicate that the Vandam Zone package was accreted between ca. 13 and 3 Ma. Following Vandam Zone accretion, thermal modeling of thermochronometric data indicates rapid exhumation (∼0.3–1 mm/yr) in the wedge interior beginning between ca. 6 and 3 Ma, and a novel thermochronometric paleo‐rotation analysis suggests out‐of‐sequence folding of wedge‐interior strata after ca. 3 Ma. Field relationships suggest that the Vandam Zone underwent syn‐convergent extension following accretion. Together, the data record spatially and temporally variable deformation, dependent on both the mechanical properties of deforming lithologies and perturbations such as accretion of material from the down‐going to the overriding plate. The diverse modes of deformation are consistent with the maintenance of critical taper. Plain Language Summary: In tectonically active mountain belts, the crust deforms internally to maintain a characteristic wedge geometry during growth. Such deformation is accommodated by a variety of mechanisms including faulting, folding, and dissolution of rock. New structural and thermochronometric data from the eastern Greater Caucasus of Azerbaijan characterize the influence of mechanical properties of deforming rock on the modes of active deformation. The eastern Greater Caucasus contains two major sedimentary rock packages with distinct lithologic properties that have been deformed via different mechanisms. The orogen interior consists of thin sandstone and shale beds deformed primarily by short‐wavelength folding. A package of thick‐bedded volcaniclastic sediment known as the Vandam Zone is deformed via slip of coherent thrust sheets. The contrasting modes of deformation that have affected these rock packages confirm the influence of lithologic properties on deformation processes and mountain belt structure. Thermochronometric data record the propagation of deformation into the Vandam Zone strata as well as subsequent deformation and accelerated exhumation within the mountain belt interior. The spatiotemporal distribution of deformation functioned to maintain the tapering wedge geometry of the deforming crust. Key Points: Pervasive folding in shale‐rich orogen interior differs from typical fold‐thrust system in thick‐bedded accreted strata of the Vandam Zone Atypical negative thermochronometric age‐elevation relationships explained as a product of fold limb rotation using novel modeling method Thermochronometric evidence for out‐of‐sequence deformation in orogen interior after Vandam Zone accretion, maintaining critical taper